Retrospective study of tadalafil for fetal growth restriction: Impact on maternal and perinatal outcomes. Issue 2 (17th December 2016) - Kubo, Michiko; Umekawa, Takashi; Maekawa, Yuka; Tanaka, Hiroaki; Nii, Masafumi; Murabayashi, Nao; Osato, Kazuhiro; Kamimoto, Yuki; Ikeda, Tomoaki
Abstract: Aim: The aim of this retrospective study was to assess tadalafil treatment in pregnant women with fetal growth restriction (FGR) in terms of maternal and perinatal outcomes. Methods: We retrospectively analyzed 11 Japanese singleton pregnant women with FGR who received tadalafil along with conventional management for FGR at Mie University Hospital from July 2015 to February 2016 (tadalafil group). These women were matched for maternal age, parity, gestational age, and estimated fetal weight at enrollment with 14 singleton pregnant women who received only the conventional management for FGR in 2014 (conventional management group). The conventional management for FGR was performed according to guidelines for obstetric practice in Japan. Results: Both birthweight and fetal growth velocity from enrollment to birth were significantly higher in the tadalafil group than in the conventional management group. The cesarean delivery rate was approximately twofold higher in the conventional management group than in the tadalafil group. Importantly, cesarean section due to non‐reassuring fetal status was performed in seven pregnant women in the conventional management group (58.3%) but in none in the tadalafil group ( P < 0.05, chi‐squared test). Conclusions: Tadalafil may improve perinatal outcome in FGR by modulating fetal growth through maintenance or improvement of fetal well‐being.